Pengendalian Kualitas Jersey dengan Menggunakan Metode Six Sigma dan Kaizen pada UMKM Titik Terang Konveksi - Roy Fajar Kusuma; Ari Zaki Al-Faritsy (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
UMKM Titik Terang Konveksi is a company that produces jersey. There are 3 types of defects, namely untidy stitching, the screen printing color is not bright enough, and the fabric is folded during the press process, which increases production costs. The purpose of this study is to determine the factors that cause defects and their solutions to minimize losses using Six Sigma and Kaizen. From 759 products October 2022 there are 109 defects. DPMO values48265.41 and valuesigma 2,933 were caused by human, machine, method, material, and environmental factors. Proposed improvements, namely providing an understanding of product quality, reprimanding employees, providing job training,. Cleaning the machine before and after use, checking machine components and replacing them if necessary, supervising operators regarding machine operation according to SOP Making SOPs, implementing SOPs continuously and continuously. Check and store good raw materials. Adding blowers, increasing ventilation, rearranging rooms used for storage and production, placing goods/tools according to their functions and uses, disposing of unused items, making tool and item shelves, expanding the building. Then the addition of 5S posters so that the work environment is always well organized. Thus, the factors that cause defects will be reduced and minimize losses.